(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2014)
The supply of medicines through court decisions is the subject of discussion among public managers, doctors and civil society, as well as in academic and legal circles. The lack of objective and clear criteria defined by case law when analyzing the granting of judicial measures further increases the controversy. This paper seeks, after a brief historical analysis, to examine the jurisprudence of the Federal Supreme Court - STF, after the holding of public hearing No. 4 and the establishment of criteria in the judgment of AgR STA 175/CE by the President of that Court, Justice Gilmar Mendes. Acts of the National Council of Justice - CNJ will then be analyzed, in view of their consistency with the established parameters and their administrative relevance to the Judiciary.